Brief Report: Comparing the Autobiographical Remembering of Iranian Immigrant Trauma Survivors with That of Iranian and British Trauma Survivors. Issue 4 (15th April 2016) - Jobson, Laura; Cheraghi, Sepideh; Moradi, Ali Reza
Summary: This study investigated how culture and posttraumatic stress disorder (PTSD) influence the autobiographical remembering of Iranian trauma survivors living in Britain compared to the remembering of British trauma survivors living in their host culture (Britain) and Iranians in their culture of origin (Iran). Iranian immigrants with and without PTSD completed measures of autobiographical remembering. Data was compared to previously collected data from British and Iranian trauma survivors with and without PTSD. It was found that the memory‐content of Iranian immigrants' memories resembled that of Iranian trauma survivors in Iran, while the phenomenological properties of their autobiographical remembering more closely resembled that of British trauma survivors. Moreover, there were pan‐cultural distortions and deficits in the autobiographical remembering of those with PTSD. The findings suggest that immigrants with PTSD have similar disruptions and distortions in their autobiographical remembering as that of individuals with PTSD living in their host culture and culture of origin.Copyright © 2016 John Wiley & Sons, Ltd.